Tendon Extracellular Matrix Remodeling and Defective Cell Polarization in the Presence of Collagen VI Mutations - Antoniel, Manuela; Traina, Francesco; Merlini, Luciano; Andrenacci, Davide; Tigani, Domenico; Santi, Spartaco; Cenni, Vittoria; Sabatelli, Patrizia; Faldini, Cesare; Squarzoni, Stefano (Cells (Basel, Switzerland), 2020)
Mutations in collagen VI genes cause two major clinical myopathies, Bethlem myopathy (BM) and Ullrich congenital muscular dystrophy (UCMD), and the rarer myosclerosis myopathy. In addition to congenital muscle weakness, patients affected by collagen VI-related myopathies show axial and proximal joint contractures, and distal joint hypermobility, which suggest the involvement of tendon function. To gain further insight into the role of collagen VI in human tendon structure and function, we performed ultrastructural, biochemical, and RT-PCR analysis on tendon biopsies and on cell cultures derived from two patients affected with BM and UCMD. In vitro studies revealed striking alterations in the collagen VI network, associated with disruption of the collagen VI-NG2 (Collagen VI-neural/glial antigen 2) axis and defects in cell polarization and migration. The organization of extracellular matrix (ECM) components, as regards collagens I and XII, was also affected, along with an increase in the active form of metalloproteinase 2 (MMP2). In agreement with the in vitro alterations, tendon biopsies from collagen VI-related myopathy patients displayed striking changes in collagen fibril morphology and cell death. These data point to a critical role of collagen VI in tendon matrix organization and cell behavior. The remodeling of the tendon matrix may contribute to the muscle dysfunction observed in BM and UCMD patients.